Active power filter integrated with distribution transformer based on magnetic potential balance. Issue 2 (18th December 2018) - Cui, Guiping; Luo, Longfu; Li, Yong; Liang, Chonggan; Zhang, Xiaofeng; Xu, Jiazhu; Liu, Yuxing; Wang, Tao; Kubis, Andreas
Abstract : In this study, magnetic potential balance based active power filter integrated with distribution transformer (DT‐APF) is proposed for harmonic reduction in distribution systems. Instead of using a step‐down transformer for voltage matching, the active power filter is connected to the taps from the secondary windings of the distribution transformer. The filtering system's integration, operating efficiency as well as reliability are significantly enhanced. The topology of the proposed DT‐APF is introduced; the compensation principle, mathematical model as well as the corresponding detection method are described in detail. A non‐linear controller based on passivity‐based control (PBC) that ensures global asymptotic stability is proposed to obtain an excellent compensation performance. To verify the feasibility and effectiveness of the presented DT‐APF and PBC in harmonic suppression, results from MATLAB simulations and experiments of a down‐scaled prototype system at laboratory are demonstrated.